ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA MATERI STATISTIKA: IMPLEMENTASI MODEL PROBLEM-BASED LEARNING - Nonoy Intan; Beni Yusepa Ginanjar Putra (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2022)
Problem solving skills are important for students to master and need to be trained and developed continuously. The purpose of this study was to find out how high school students' mathematical problem solving abilities in Statistics material with the implementation of Problem-Based Learning. This type of research is qualitative descriptive research. The subjects of this research were class XII students of SMA Negeri 5 Cimahi. The sample in this study were 30 students of class XII IPA 3, with 22 female students and 8 male students. The research time is the first semester of the 2022-2023 Academic Year. Collecting data in this study used a test instrument for mathematical problem solving abilities in the Quartile submatter Statistics material. Data analysis techniques were carried out with the stages of data reduction, data presentation, and drawing conclusions. The results of this study indicate that the percentage of achievement of mathematical problem solving abilities of class XII high school students in Statistics material which is classified as Very Good (SB) is 26.7%, while the achievement category that dominates is the Enough category (C), namely 53.3%.